2011
DOI: 10.1074/jbc.m110.184101
|View full text |Cite
|
Sign up to set email alerts
|

FXYD Proteins Reverse Inhibition of the Na+-K+ Pump Mediated by Glutathionylation of Its β1 Subunit

Abstract: We have reported that Na ؉ -K ؉ pump ␤ 1 subunit glutathionylation induced by oxidative signals causes pump inhibition in a previous study. In the present study, we found that ␤ 1 subunit glutathionylation and pump inhibition could be reversed by exposing myocytes to exogenous wild-type FXYD3. A cysteine-free FXYD3 derivative had no effect. Similar results were obtained with wild-type and mutant FXYD proteins expressed in oocytes. Glutathionylation of the ␤ 1 subunit was increased in myocardium from FXYD1 ؊/؊ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
115
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 44 publications
7
115
1
Order By: Relevance
“…Inhibition of GRX1 under oxidative stress has also been suggested by Heshemy et al [28]. To ascertain the role of PLM in this scenario, we performed studies with liposomes recon- [12] showed that the ATPase activity was proportional with the level of glutathionylation of the pump, but we have not found such proportionality after treatment of the cells with U46619. It is also well established that oxidant stress during ischemic condition may cause accumulation of substances that inhibit membrane transporter such as NKA.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Inhibition of GRX1 under oxidative stress has also been suggested by Heshemy et al [28]. To ascertain the role of PLM in this scenario, we performed studies with liposomes recon- [12] showed that the ATPase activity was proportional with the level of glutathionylation of the pump, but we have not found such proportionality after treatment of the cells with U46619. It is also well established that oxidant stress during ischemic condition may cause accumulation of substances that inhibit membrane transporter such as NKA.…”
Section: Discussionmentioning
confidence: 82%
“…2B, lane 1), but the expected glutathionylation signal was quite different after its inhibition. Bibert et al [12] showed that recombinant FXYD3 facilitated the deglutathionylation of NKA in Xenopus oocytes. We found that glutathionylation of PLM was induced from baseline by exposing the cells to U46619.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the application of peroxynitrite (ONOO -) or Snitrosoglutathione (GSNO, 10-500 lM) to induce S-glutathionylation is also found in the literature (12,38,125,129). The application of peroxynitrite is of high physiological relevance but as peroxynitrite can also induce other modification including S-nitrosylation, additional experiments should be performed to further dissect the exact modification mechanism.…”
Section: Induction Of S-glutathionylationmentioning
confidence: 99%